The Influence of the Presence of Iron in Highly Alkaline Polyaluminium Chlorides on the Effectiveness of Precursors of Disinfection By-Products Removal - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The mechanism of coagulation with highly alkaline polyaluminum chlorides is well understood, but there is a lack of information on the effect of the presence of iron in these coagulants on the efficiency of purifying water with increased contents of natural organic matters among which humic substances are precursors of disinfection by-products.
Keywords: highly alkaline polyaluminium chlorides; organic substances; fulvic acids; iron-organic complexes; protective colloids